2007
DOI: 10.1142/s0218810407003535
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Tendon Sheath Injection for Trigger Finger: The Randomized Controlled Trial

Abstract: The most common technique used for non-surgical treatment of trigger fingers is the direct injection of steroids into the flexor tendon sheath over the metacarpal head. However, this method causes more pian to the patient and can result in tendon rupture due to insertion of needle into the tendon. Carlson and Curtis described the mid-axial injection technique which is simple and relatively painless. We aim to compare the pain result from the injection between these two methods. The prospective randomised contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Some researchers have used closed treatment with steroids and narcotic drugs to treat it [6,7], but the effect is not ideal and often causes tendon rupture [8,9]. Some surgeons reported that they treated stenosing tenosynovitis of the thumb with a mini-scalpel needle and achieved good effect, but with mini-scalpel needle surgery it is very easy to damage nerves, blood vessels, and tendons, in which case repeated surgery may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have used closed treatment with steroids and narcotic drugs to treat it [6,7], but the effect is not ideal and often causes tendon rupture [8,9]. Some surgeons reported that they treated stenosing tenosynovitis of the thumb with a mini-scalpel needle and achieved good effect, but with mini-scalpel needle surgery it is very easy to damage nerves, blood vessels, and tendons, in which case repeated surgery may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…54 A modification of that technique is to inject extra-synovial superficial to the tendon sheath. The least painful approach may be to inject the proximal phalangeal portion of the tendon sheath through a lateral approach while carefully avoiding the neurovascular bundle 66,67 ; but this technique is technically more difficult for those infrequently performing such injections. A fourth method and the one we use and teach to our learners in our procedure clinic is a simple, safe entry over the volar proximal phalanx through the tendon to inject into the posterior (deep) space between tendon and sheath without US guidance as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…52 There have been anecdotal case reports of tendon rupture, pulley rupture, and digital ischaemia. [49][50][51][52][53][54][55][56][57][58][59][60][61] Morbidity with injection is far less than with open surgery, and time off work or sports is quoted at three days compared with 26 days, respectively. 62 Early recurrence within three months was 33% in one large series of 1210 trigger injections, 47 and 55% at 1 year 63 -though this might be reduced with concurrent physiotherapy.…”
Section: Steroid Injectionmentioning
confidence: 99%